Pengaruh Pendekatan Pembelajaran Responsive Budaya terhadap Hasil Belajar Matematika Siwa Kelas 5 di SDN 26 Cakranegara - Nurfitriana, Saumi; Affandi, Lalu Hamdian; Tahir, Muhammad (Mataram University, 2026)
This study aimed to determine the effect of a culturally responsive teaching approach on the mathematics learning outcomes of fifth-grade students at SDN 26 Cakranegara on the topic of fractions. The research employed a quantitative approach using a quasi-experimental method with a Nonequivalent Control Group Design. The research subjects consisted of two classes: Class 5A as the experimental group and Class 5B as the control group, with a total of 60 students. The research instrument was a multiple-choice test that had been tested for validity and reliability. Data analysis was conducted through normality testing, homogeneity testing, and the Independent Sample t-test. The results showed that the significance value (Sig. 2-tailed) was < 0.05, indicating a significant difference between the experimental and control groups. Therefore, the culturally responsive teaching approach had a positive and significant effect on improving students’ mathematics learning outcomes.